Judah and the Judeans in the Persian Period - Amit, Yairah; Becking, Bob; Berquist, Jon L; Blenkinsopp, J; Dandamayev, M. A; Edelman, Diana; Eskenazi, Tamara Cohn 1938-; Fantalkin, Alexander; Fried, Lisbeth S; Grabbe, Lester L; Japhet, Sara; Kessler, John; et al. (University Park, PA Penn State University Press, 2021)
Frontmatter -- Contents -- Introduction -- Abbreviations -- Part 1 Historical, Epigraphical, and Archaeological Perspectives -- "We All Returned as One!": Critical Notes on the Myth of the Mass Return -- Achaemenid Imperial Policy, Settlement Processes in Palestine, and the Status of Jerusalem in the Middle of the Fifth Century b.c.e. -- Constructions of Identity in Postcolonial Yehud -- Remapping Yehud: The Borders of Yehud and the Genealogies of Chronicles -- Persia's Loyal Yahwists: Power Identity and Ethnicity in Achaemenid Yehud -- The 'am hā'āreṣ in Ezra 4:4 and Persian Imperial Administration -- The Borders and De Facto Size of Jerusalem in the Persian Period -- Redating Lachish Level I: Identifying Achaemenid Imperial Policy at the Southern Frontier of the Fifth Satrapy -- The Religious Revolution in Persian-Period Judah -- Tyrian Trade in Yehud under Artaxerxes I: Real or Fictional? Independent or Crown Endorsed? -- The Second Temple of Jeb and of Jerusalem -- Revisiting the Samarian Question in the Persian Period -- Bethel: The Israelite Impact on Judean Language and Literature -- Cyrus II, Liberator or Conqueror? Ancient Historiography concerning Cyrus in Babylon -- Neo-Babylonian and Achaemenid State Administration in Mesopotamia -- New Evidence for Judeans in Babylonia -- New Aramaic Ostraca from Idumea and Their Historical Interpretation -- Social, Economic, and Onomastic Issues in the Aramaic Ostraca of the Fourth Century b.c.e. -- Part 2 Biblical Perspectives -- Periodization between History and Ideology II: Chronology and Ideology in Ezra-Nehemiah -- The Missions of Ezra and Nehemiah -- The "Persian Documents" in the Book of Ezra: Are They Authentic? -- "See, We Are Serving Today" (Nehemiah 9:36): Nehemiah 9 as a Theological Interpretation of the Persian Period -- Sociolinguistics and the Judean Speech Community in the Achaemenid Empire -- Benjamin Traditions Read in the Early Persian Period -- The Saul Polemic in the Persian Period -- The Imaginary Sanctuary: The Priestly Code as an Example of Fictional Literature in the Hebrew Bible -- Index of Authors -- Index of Scripture -- Index of Sites and Place-Names
In July 2003, a conference was held at the University of Heidelberg (Germany), focusing on the people and land of Judah during the 5th and early 4th centuries B.C.E.- the period when the Persian Empire held sway over the entire ancient Near East. This volume publishes the papers of the participants in the working group that attended the Heidelberg conference.Participants whose contributions appear here include: Y. Amit, B. Becking, J. Berquist, J. Blenkinsopp, M. Dandamayev, D. Edelman, T. Eskenazi, A. Fantalkin and O. Tal, L. Fried, L. Grabbe, S. Japhet, J. Kessler, E. A. Knauf, G. Knoppers, R. Kratz, A. Lemaire, O. Lipschits, H. Liss, M. Oeming, L. Pearce, F. Polak, B. Porten and A. Yardeni, E. Stern, D. Ussishkin, D. Vanderhooft, and J. Wright.The conference was the second of three meetings; the first, held at Tel Aviv in May 2001, was published as Judah and the Judeans in the Neo-Babylonian Period by Eisenbrauns in 2003. A third conference focusing on Judah and the Judeans in the Hellenistic era was held in the summer of 2005, at Münster, Germany, and will also be published by Eisenbrauns
[Online-Ausgabe]
Mode of access: Internet via World Wide Web.
In English
Archivierung/Langzeitarchivierung gewährleistet
Keywords: HISTORY / Ancient / General; HISTORY / Middle East / Israel & Palestine